MENGUJI KEPEDULIAN SISWA SMPN 10 MUARO JAMBI TERHADAP LINGKUNNGAN (Universitas PGRI Sumatera Barat, 2020)
Education has a very important role in educating the life of the nation. Education should not only shape someone who is an expert in a particular field, but also how a person is able to bring himself into the environment of society, nation and state in accordance with the applicable norms and rules. However, education that occurs now still does not provide space for students to behave honestly because the learning process tends to teach moral education and character as limited to the knowledge written in the text. Therefore, this study was designed to see the environmental care of students, especially junior high school students, because they are a transition from children to adolescents, a time when individuals become very unstable, and easily imitate whatever he sees in his environment. This study uses a type of survey research. This research data uses quantitative data. The technique of data collection is done through the provision of instruments, namely questionnaires. The respondents in this study were junior high school students, amounting to 50 respondents, of which the respondents were students from class VII-A and VII-b SMPN 10 Muaro Jambi. the results of this study students' tolerance attitude is very good.